Reducing inequalities and strengthening social cohesion through inclusive growth: A roadmap for action - Romina Boarini; Orsetta Causa; Marc Fleurbaey; Gianluca Grimalda; Ingrid Woolard (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
The authors propose a policy compact to achieve more inclusive growth in G20 countries so that economic growth regains the ultimate sense of improving all people's lives. Guiding principles are: 1) prosperity is not just about income but about all relevant outcomes of well-being and capabilities to overcome the initial social disadvantage; 2) it is also about including people in participatory decision-making to enhance their dignity and control over their lives; 3) excluding people from reaping the benefits of growth will thwart social cohesion and well-being; 4) integrated policy approaches are needed to achieve inclusive growth, across policy domains and between national and global actions, including responsible management of migratory movements. Concrete policy actions are described that span education, labor, fiscal instruments, public and private governance.
Keywords: D63; O40; E60; 330; Inclusive growth; social cohesion; inequalities; well-being